A single topical dose of erythropoietin applied on a collagen carrier enhances calvarial bone healing in pigs. (April 2014) - Rölfing, Jan Hendrik Duedal; Jensen, Jonas; Jensen, Julie Neerup; Greve, Anne-Sofie; Lysdahl, Helle; Chen, Muwan; Rejnmark, Lars; Bünger, Cody
<x xml:space="preserve">Abstract</x> Background and purpose — The osteogenic potency of erythropoietin (EPO) has been documented. However, its efficacy in a large-animal model has not yet been investigated; nor has a clinically safe dosage. The purpose of this study was to overcome such limitations of previous studies and thereby pave the way for possible clinical application. Our hypothesis was that EPO increases calvarial bone healing compared to a saline control in the same subject. Methods — We used a porcine calvarial defect model. In each of 18 pigs, 6 cylindrical defects (diameter: 1 cm; height: 1 cm) were drilled, allowing 3 pairwise comparisons. Treatment consisted of either 900 IU/mL EPO or an equal volume of saline in combination with either autograft, a collagen carrier, or a polycaprolactone (PCL) scaffold. After an observation time of 5 weeks, the primary outcome (bone volume fraction (BV/TV)) was assessed with high-resolution quantitative computed tomography. Secondary outcome measures were histomorphometry and blood samples. Results — The median BV/TV ratio of the EPO-treated collagen group was 1.06 (CI: 1.02–1.11) relative to the saline-treated collagen group. Histomorphometry showed a similar median effect size, but it did not reach statistical significance. Autograft treatment had excellent healing potential and was able to completely regenerate the bone defect independently of EPO treatment. Bony ingrowth into the PCL scaffold was sparse, both with and without EPO. Neither a substantial systemic effect nor adverse events were observed. The number of blood vessels was similar in EPO-treated defects and saline-treated defects. Interpretation — Topical administration of EPO on a collagen carrier moderately increased bone healing. The dosing regime was safe, and could have possible application in the clinical setting. However, in order to increase the clinical relevance, a more potent but still clinically safe dose should be investigated.